PEMBENTUKAN KETERAMPILAN KOMUNIKASI DAN KOLABORASI MELALUI BUKU AJAR DOKUSAKU I - Syaifia, Balqis (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2023)
This study aims to find out how to build students' 21st century communication and collaboration skills through the use of the Dokusaku I textbook "Nobinobi Yomikaki". The emergence of the COVID-19 pandemic which affected learning activities greatly affected the skills of students. Meanwhile, the demand for skills in surviving the challenges of 21st century life is increasing rapidly. This is the background of this research, therefore the researcher conducts research on the formation of 21st century skills in students through textbooks that have been developed according to 21st century skills. The analysis in this study refers to the criteria for aspects of communication and collaboration skills put forward by Fadel and Triling, also based on the theory of communication and collaboration skills approach by Masukawa. The method used is observation and documentation, while the analysis technique used is descriptive qualitative. The findings from this study are the formation of communication and collaboration skills using the Dokusaku I textbook "Nobinobi Yomikaki". Communication and collaboration skills most often occur in the hanashiaimashou (let's discuss) sub-chapter, because this sub-chapter contains all the indicators of both skills. Not just talking, but fulfilling the essential criteria of communication and collaboration skills.